Neovascular Glaucoma from Ocular Ischemic Syndrome Treated with Serial Monthly Intravitreal Bevacizumab and Panretinal Photocoagulation: A Case Report - Hassaan Asif; Zhuangjun Si; Steven Quan; Pathik Amin; David Dao; Lincoln Shaw; Dimitra Skondra; Mary Qiu (Case Reports in Ophthalmological Medicine)
Purpose. To describe a case of open-angle neovascular glaucoma (NVG) secondary to ocular ischemic syndrome (OIS) treated with a planned series of 6 monthly anti-VEGF injections with interspersed panretinal photocoagulation (PRP) sessions. We term this treatment protocol the Salvaging Conventional Outflow Pathway in Neovascular Glaucoma (SCOPING) Protocol, and this is our (MQ and DS) standard of care for all NVG patients presenting with partially or completely open angles. Case. A 66-year-old man’s right eye had a visual acuity of 20/50, intraocular pressure (IOP) of 42 mmHg on 0 IOP-lowering medications, and neovascularization of the iris and angle with no peripheral anterior synechiae. Fundoscopy revealed midperipheral dot-blot hemorrhages without diabetic retinopathy or vein occlusion. Fluorescein angiography revealed peripheral retinal nonperfusion in both eyes. The patient was diagnosed with open-angle NVG secondary to OIS and treated with 6 serial monthly anti-VEGF injections interspersed with 4 PRP sessions, after which his anterior segment neovascularization regressed and IOP normalized on 0 medications. Ten weeks after the last injection, the anterior segment neovascularization and elevated IOP recurred, so he underwent 4 more monthly anti-VEGF injections and 4 PRP sessions, after which his anterior segment neovascularization regressed and his IOP normalized on 0 medications. However, 6 weeks after the last injection, the anterior segment neovascularization and elevated IOP again recurred, so he was resumed on a third course of lifetime monthly anti-VEGF injections, which may be continued in perpetuity. Conclusion. The patient’s NVG was quiescent while under the protection of serial anti-VEGF injections with interspersed PRP; however, the disease recurred each time injections were stopped. Therefore, in patients with open-angle NVG secondary to OIS, serial monthly anti-VEGF injections may be necessary combined with PRP to suppress underlying neovascular drive and regress anterior segment neovascularization, maintain physiologic IOP, and prevent synechial angle closure.